Quantitative Study of Startup Valuation and Strategy Post 2022 Winter - Fajrin Rasyid, Muhamad; Sumirat, Erman; Aswin Rahadi, Raden (Riviera Publishing, 2023)
Introduction: In 2022, the market capitalization of some publicly traded technology companies is declining. This period is commonly referred to as